FEASIBILITY STUDY OF THE BIOTECHNOLOGY PRODUCTION PROJECT - Башлай, Сергій; Коваленко, Владислав (Modern engineering and innovative technologies, 2024)
This paper discusses some aspects of the need and opportunities to introduce and use new alternative means of energy production. Given the almost inexhaustible raw material resources, biotechnology is attracting more and more attention around the world. T